Metaphor-Based Visual Media for Cell Biology Instruction: Effects on Students' Science Literacy and Metacognitive Skills - Wibowo, Jayaman; Hindriana, Anna Fitria; Abidin, Zaenal (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Cell biology is widely regarded as one of the most conceptually challenging topics in secondary science education due to the microscopic and abstract nature of its structures and processes. This study developed and evaluated metaphor-based visual instructional media designed to transform abstract cellular concepts into contextually accessible visual representations using the ADDIE instructional design model (Analysis, Design, Development, Implementation, and Evaluation), combined with a quasi-experimental pretest–posttest control group design. Sixty Grade VIII students (n = 30 experimental; n = 30 control) at SMPN 1 Plumbon, Cirebon Regency, Indonesia participated in the study. The experimental group received instruction via the developed metaphor-based visual media — in which cellular organelles were systematically mapped onto familiar household elements — while the control group received conventional instruction. Data were collected using a science literacy test, a Metacognitive Awareness Inventory (MAI) questionnaire, and a student response survey. The experimental class demonstrated substantially greater learning gains (pretest M = 62.68; posttest M = 89.83) compared with the control class (pretest M = 60.46; posttest M = 76.90). Normalized gain (N-Gain) analysis confirmed that 78% of experimental class students achieved high N-Gain scores, versus 0% in the control class. Multiple regression analysis revealed significant positive associations: visual metaphor media and science literacy (r = 0.521, p = .001); metacognitive skills and science literacy (r = 0.585, p < .001); and visual metaphor media and metacognitive skills (r = 0.411, p = .010). Expert validation rated the media at an overall mean of 91.03%, classified as ‘very suitable.’ These findings demonstrate that metaphor-based visual media constitute an effective, theoretically grounded instructional strategy for simultaneously advancing science literacy and metacognitive skills in junior high school biology education.